Penerapan Kurikulum 2013 Revisi 2018 dalam Meningkatkan Prestasi Belajar Siswa: Studi Multi Situs di SMP Raden Fatah Batu dan MTs. Ihyaul Ulum Dukun Gresik - Machrus Salim; Nila Mujtahidah (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2020)
The study aim at investigating the process of planning, implementing, and evaluating of the Revised 2013 Curriculum year 2018 to improve the students' achievement. The study was case study research with multi case study design as the objects of the study had some similarities. The data sources were the results of conducting interviews, documentations, and observations. The data analysis included data reduction, data display, and conclusion drawing. The data were verified using data sources triangulation.The result showed: 1) The planning at SMP Raden Fatah Batu and MTs Ihyaul Ulum Gresik was initiated by comprehending the existing syllabus, mapping the main and basic competence as well as the success indicators for each subject. The involvement of the teachers in The Teacher Association Forum was maximized to share ideas and conform the planning. 2) In implementing, both schools involved the associated basic competence and current issues, created pleasant and conducive learning, used learning media, and involved the parents which were effective in improving the students' achievement. 3) The evaluation was conducted comprehensively and factually. The students' achievement was identified continually on all of the aspects of learning and it involved teacher-counselor The final score was derived from the averaged total score.